Research in personnel and human resources management. Vol. 20 - Ferris, Gina (Emerald, 2001)
This volume is part of a series which publishes monograph length conceptual papers designed to promote theory and research on important substantive and methodological topics in the field of human resources management.
Keywords: Business & Economics -- Management.; Science -- History.; Personnel & human resources management.; Personnel management.; elektronické knihy; electronic books